A nickel-cobalt-based core-shell catalyst and its preparation method and application in assembling zinc-ethanol-air batteries
The nickel-cobalt-based core-shell catalyst prepared by electrochemical methods solves the problem of slow kinetics and easy poisoning of existing EOR catalysts by optimizing the adsorption energy of *OH, and achieves an efficient and stable ethanol oxidation reaction, which is suitable for zinc- Ethanol-air battery high power density and stability.
Patent Information
- Application Number
- CN202411614083.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The kinetics of existing ethanol oxidation reactions (EOR) catalysts are slow, precious metal reserves and costs limit large-scale applications, and catalysts are prone to poisoning, resulting in reduced activity.
The nickel-cobalt-based core-shell catalyst was prepared by electrochemical methods. The nickel-cobalt-tin alloy was used as the core and nickel-cobalt-hydroxyoxide as the shell, and the adsorption energy of *OH was optimized to promote the EOR reaction.
It achieves a large current density at a lower electric potential, has excellent electrocatalytic activity and stability in ethanol oxidation reaction, and exhibits high power density and excellent charge and discharge activity in zinc-ethanol-air batteries.
Smart Images

Figure CN119153713B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of an ethanol oxidation reaction electrocatalyst and zinc-ethanol-air battery, and specifically relates to a nickel-cobalt-based core-shell catalyst and a preparation method thereof and application in assembling a zinc-ethanol-air battery. Background Art
[0002] Rechargeable zinc-air batteries (RZABs) have attracted much attention due to their high energy density, low cost, and good safety. They are of great significance in alleviating the current energy shortage and improving environmental quality. However, RZABs also face many challenges. For example, during the charging process, the oxygen evolution reaction (OER) occurs at the air electrode, which has very slow kinetics and often requires a large overpotential to proceed. In addition, even at lower current densities, abundant oxygen bubbles are generated and attached to the surface of the air electrode, occupying the catalytic active sites, hindering the contact of the reaction substrate, and even causing the catalyst to fall off ( Energy Storage Mater. 2023, 57, 360–370), which has an extremely adverse effect on the charging efficiency and stability of RZABs.
[0003] Using thermodynamically more feasible organic small molecule oxidation to replace OER can not only reduce the energy consumption of the reaction, but also avoid the adsorption of oxygen bubbles, and also obtain high value-added organic compounds. As a renewable biomass liquid fuel, ethanol has the advantages of being non-toxic, cheap, abundant in source, high in hydrogen content, high in energy density, easy to store and transport, etc. It is an ideal energy carrier, so ethanol oxidation reaction (EOR) has attracted the research interest of many scientists in recent years and is expected to be used to replace the OER reaction in the charging process of RZABs. Considering that EOR is a complex multi-step proton-coupled electron transfer process with slow kinetics, the EOR catalysts currently used are mostly based on precious metals, and their reserves and costs limit large-scale applications. Therefore, the development of highly active, highly stable, economical and inexpensive non-precious metal EOR electrocatalysts is a technical problem that needs to be solved urgently.
[0004] EOR usually has two competing reaction pathways, C1 and C2. For example, the C1 pathway completely oxidizes ethanol to CO2 through a 12-electron process, but the deep oxidation process is accompanied by CH xThe C2 pathway involves the incomplete oxidation of ethanol, which generates acetate through a 4-electron process, which not only reduces the possibility of catalyst poisoning, but also generates high-value acetate. Therefore, the development of catalysts with simple synthesis methods, stable structures, low costs, and high activity is of great significance for the research of electrode materials for ethanol oxidation reactions.
[0005] In the catalytic EOR process, the adsorbed hydroxyl groups (*OH) on the catalyst surface are believed to have an important influence on the proton transfer and dehydrogenation of carbon-based intermediates ( Nano Res. 2024, 17(5), 3863–3871), which can effectively prevent the "poisoning" of the catalyst. Since the adsorption strength of transition metal elements such as Ni and Co on *OH is different, the adsorption energy of *OH can be optimized based on NiCo-based catalysts, and efficient and stable catalysis of EOR can be achieved. In addition, the specific surface area and conductivity of the catalyst are also important factors affecting the catalytic activity ( Adv. Sci. 2020, 7, 1903777). Therefore, the present invention proposes a method for preparing NiCoSn@NiCoOOH core-shell nanomaterials based on an electrochemical method, and exhibits excellent EOR electrocatalytic activity and selectivity. There is no related report in this regard. Summary of the invention
[0006] The technical problem solved by the present invention is to provide a nickel-cobalt-based core-shell catalyst and a preparation method thereof. The method prepares a nickel-cobalt-tin alloy by an electrodeposition method and obtains a nickel-cobalt hydroxyl oxide from the nickel-cobalt-tin alloy by an anodic oxidation method to obtain a nickel-cobalt-based core-shell nanomaterial. The nickel-cobalt-based core-shell nanomaterial grows tightly on a carbon cloth substrate, avoiding the use of a conductive adhesive. The nickel-cobalt-based core-shell nanomaterial uses a nickel-cobalt-tin alloy as a core to ensure rapid charge transfer, and uses a defect-rich nickel-cobalt hydroxyl oxide as an outer shell to provide abundant active sites. At the same time, the synergistic effect of nickel and cobalt optimizes the adsorption energy of *OH, promotes the EOR reaction through the C2 pathway, and enables the nickel-cobalt-based core-shell nanomaterial to reach 246mA cm at a potential of 1.56V. −2 The current density is high, and it has good electrocatalytic activity for ethanol oxidation reaction. The zinc-ethanol-air battery assembled with nickel-cobalt-based core-shell nanomaterials as electrocatalysts has a charging voltage of only 1.79V, which is much lower than that of zinc-air batteries (2.1V), and can maintain the excellent stability of the battery.
[0007] The present invention adopts the following technical scheme to solve the above technical problems. A method for preparing a nickel-cobalt-based core-shell catalyst is characterized in that the specific steps are: dissolving a soluble nickel salt, a soluble cobalt salt, a soluble tin salt and a soluble citrate in deionized water, stirring and mixing to obtain a mixed solution, using the mixed solution as an electrolyte, adopting a three-electrode system, using a pretreated carbon cloth as a working electrode, and performing constant voltage electrolytic deposition. The voltage range during the constant voltage electrolytic deposition process is 0~-0.4V vs RHE, and the deposition charge is controlled to be 1-8C / cm 2 A nickel-cobalt-tin alloy nanomaterial is generated on the surface of the carbon cloth electrode, and then anodized in an alkaline solution to obtain a nickel-cobalt-based core-shell catalyst, wherein the anodization time is 0.5-3h and the anodization current density is 5-20mA / cm 2 The nickel-cobalt-based core-shell catalyst is used for electrocatalytic ethanol oxidation reaction to produce acetic acid.
[0008] It is further defined that the soluble nickel salt is one or more of nickel sulfate, nickel acetate or nickel nitrate; the soluble cobalt salt is one or more of cobalt sulfate, cobalt acetate or cobalt nitrate; the soluble tin salt is one or more of tin chloride and stannous chloride; the soluble citrate is one or more of sodium citrate or potassium citrate.
[0009] It is further defined that the molar ratio of the soluble nickel salt, the soluble cobalt salt and the soluble tin salt is 1:1:2.
[0010] It is further defined that the concentrations of the soluble nickel salt and the soluble cobalt salt are both 10-200 mM.
[0011] It is further defined that in the three-electrode system, the graphite rod is used as the counter electrode and the silver / silver chloride electrode is used as the reference electrode.
[0012] It is further defined that the alkaline solution is one or more of a sodium hydroxide solution or a potassium hydroxide solution, and the concentration of the alkaline solution is 0.1-2M.
[0013] A nickel-cobalt-based core-shell catalyst, characterized in that it is prepared by the above method, the nickel-cobalt-based core-shell catalyst has a unique composition and structure, and its morphology is nanoparticles with NiCoSn alloy as the core and NiCoOOH as the shell.
[0014] The nickel-cobalt-based core-shell catalyst of the present invention is used as an electrocatalyst for ethanol oxidation reaction. The nickel-cobalt-based core-shell catalyst is directly grown on carbon cloth. The core NiCoSn alloy of the nickel-cobalt-based core-shell catalyst can improve good electrical conductivity and ensure fast and efficient carrier transmission. The shell NiCoOOH can optimize the adsorption energy of *OH, and the shell is rich in defects, which can increase the active specific surface area. Therefore, the nickel-cobalt-based core-shell catalyst exhibits a lower onset potential, a higher catalytic current and better reaction selectivity under alkaline conditions, so it has excellent electrocatalytic activity for ethanol oxidation reaction.
[0015] The nickel-cobalt-based core-shell catalyst of the present invention is used in the assembly of zinc-ethanol-air batteries. The assembled zinc-ethanol-air batteries show excellent charge-discharge activity and cycle stability during the charge-discharge process, and the power density is as high as 2.5 mW cm −2 .
[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0017] 1. The nickel-cobalt-based core-shell catalyst prepared by the present invention has simple and easily available raw materials, low cost, and is non-toxic and harmless; the required conditions are relatively mild, the required equipment is relatively conventional, and it is easy to prepare and regulate.
[0018] 2. The nickel-cobalt-based core-shell catalyst prepared by the present invention has the morphology of nanoparticles with uniform size, which ensures the high activity and stability of the material.
[0019] 3. The nickel-cobalt-based core-shell catalyst prepared by the present invention is integrated with the carbon cloth substrate, ensuring the rapid transfer of carriers.
[0020] 4. The unique composition and structure of the nickel-cobalt-based core-shell catalyst prepared by the present invention greatly improve the catalytic EOR performance. For example, the nickel-cobalt-based core-shell catalyst can reach 246 mA cm at 1.56 V vs RHE. −2 of current density.
[0021] 5. The zinc-ethanol-oxygen battery assembled based on the nickel-cobalt-based core-shell catalyst prepared by the present invention can be charged at a relatively low voltage, for example, the charging voltage is only 1.79V, which is much lower than the charging voltage of the zinc-air battery (2.1V), and can achieve excellent stability.
[0022] The nickel-cobalt-based core-shell catalyst proposed in the present invention, based on its unique composition and core-shell structure, and the construction of an integrated self-supporting electrode, can effectively optimize the adsorption energy of *OH, promote electron transport and transfer, and provide abundant active sites, thereby achieving a larger current density at a lower potential and having excellent EOR electrocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the X-ray diffraction pattern of the nickel-cobalt-tin alloy nanoparticles obtained in Example 1.
[0024] Figure 2 This is a scanning electron microscope image of the nickel-cobalt-based core-shell nanomaterial prepared in Example 1.
[0025] Figure 3 This is the Ni 2p X-ray photoelectron spectrum of the outer shell of the nickel-cobalt-based core-shell nanomaterial prepared in Example 1.
[0026] Figure 4 This is the Co 2p X-ray photoelectron spectrum of the outer shell of the nickel-cobalt-based core-shell nanomaterial prepared in Example 1.
[0027] Figure 5 This is the Ni 2p X-ray photoelectron spectrum of the inner core of the nickel-cobalt-based core-shell nanomaterial prepared in Example 1.
[0028] Figure 6 This is the Co 2p X-ray photoelectron spectrum of the inner core of the nickel-cobalt-based core-shell nanomaterial prepared in Example 1.
[0029] Figure 7 This is a linear sweep voltammetry curve of the nickel-cobalt-based core-shell nanomaterial prepared in Example 1 in 1M potassium hydroxide and 1M potassium hydroxide + 1M ethanol.
[0030] Figure 8 The NMR images of the products obtained by electrolyzing the nickel-cobalt-based core-shell nanomaterials prepared in Example 1 at different voltages.
[0031] Fig. 9 The linear scanning voltammetry curves of nickel-cobalt-based core-shell nanomaterials, nickel-based core-shell nanomaterials, and cobalt-based core-shell nanomaterials prepared in Example 1, Comparative Example 1, and Comparative Example 2 in 1M potassium hydroxide + 1M ethanol are shown.
[0032] Fig.10 The charge and discharge curves of the zinc-air battery and zinc-ethanol-air battery assembled with nickel-cobalt-based core-shell nanomaterials prepared in Example 1 are shown. DETAILED DESCRIPTION
[0033] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example 1
[0034] Preparation of Ni-Co-Tin Alloy Nanoparticles:
[0035] Nickel-cobalt-tin alloy nanoparticles were synthesized in one step by an electrochemical method. The specific process was as follows: 87.2 mg of nickel nitrate, 87.3 mg of cobalt nitrate, 210.4 mg of tin tetrachloride and 882.3 mg of sodium citrate were dissolved in 30 mL of deionized water, and the mixture was stirred and mixed to obtain a mixed solution; the obtained mixed solution was used as an electrolyte, the pretreated carbon cloth was used as a working electrode, a graphite rod was used as a counter electrode, and a silver / silver chloride electrode was used as a reference electrode, and NiCoSn was prepared by a constant voltage method, wherein the voltage was -0.2 V vs RHE, and the electrolysis was stopped when the deposited charge reached 1 C, and the carbon cloth electrode was rinsed with deionized water, and then dried at room temperature to obtain NiCoSn alloy nanoparticles.
[0036] The X-ray diffraction pattern of the nickel-cobalt-tin alloy nanoparticles finally obtained is shown in the attached figure. Figure 1 As shown, with Ni 0.75 Co 0.75 Sn 0.75 The results are consistent with the standard card (27-1119), proving the successful preparation of nickel-cobalt-tin alloy.
[0037] Preparation of nickel-cobalt based core-shell nanomaterials:
[0038] The nickel-cobalt-based core-shell nanomaterials were synthesized by an anodic oxidation method. The specific process was as follows: the carbon cloth electrode loaded with nickel-cobalt-tin alloy nanoparticles prepared above was used as the working electrode, the graphite rod was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode. The reaction was carried out in a 1 M KOH solution at 10 mA cm −2 The electrolysis was carried out for 2 h at a current density of 1.500 N. The carbon cloth electrode was rinsed with deionized water and then heated at 60 o C is dried to obtain nickel-cobalt based core-shell nanomaterials.
[0039] The scanning electron microscope image of the final nickel-cobalt-based core-shell nanomaterial is shown in the attached figure. Figure 2 shown.
[0040] Comparative Example 1
[0041] Preparation of nickel-based core-shell nanomaterials:
[0042] The nickel-based core-shell nanomaterials were synthesized by electrochemical method. The specific process was as follows: 87.2 mg nickel nitrate, 210.4 mg tin tetrachloride and 882.3 mg sodium citrate were dissolved in 30 mL deionized water, and the mixture was stirred to obtain a mixed solution; the obtained mixed solution was used as an electrolyte, the pretreated carbon cloth was used as a working electrode, the graphite rod was used as a counter electrode, and the silver / silver chloride electrode was used as a reference electrode. The constant voltage method was used to prepare NiSn, wherein the voltage was -0.2 V vs RHE. When the deposited charge reached 1 C, the electrolysis was stopped, and the carbon cloth electrode was rinsed with deionized water. Subsequently, the nickel-tin material was placed in a 1 M KOH solution at 10 mA cm −2The nickel-based core-shell nanomaterials were obtained by electrolysis at a current density of 2 h, rinsing the carbon cloth electrode with deionized water, and then drying at 60 °C.
[0043] Comparative Example 2
[0044] Preparation of cobalt-based core-shell nanomaterials:
[0045] Cobalt-based core-shell nanomaterials were synthesized by electrochemical method. The specific process was as follows: 87.3 mg of cobalt nitrate, 210.4 mg of tin tetrachloride and 882.3 mg of sodium citrate were dissolved in 30 mL of deionized water, and the mixture was stirred to obtain a mixed solution. The obtained mixed solution was used as an electrolyte, the pretreated carbon cloth was used as a working electrode, the graphite rod was used as a counter electrode, and the silver / silver chloride electrode was used as a reference electrode. CoSn was prepared by constant voltage method, wherein the voltage was -0.2 V vs RHE. When the deposited charge reached 1 C, the electrolysis was stopped, and the carbon cloth electrode was rinsed with deionized water. Then, the cobalt-tin material was placed in 1 M KOH solution at 10 mA cm −2 The electrolysis was carried out at a current density of 2 h, and the carbon cloth electrode was rinsed with deionized water, and then dried at 60 °C to obtain the cobalt-based core-shell nanomaterial.
[0046] The X-ray photoelectron spectrum of the nickel-cobalt-based core-shell nanomaterial prepared in Example 1 is as follows: Figures 3 to 6 As shown, Figure 3 and Figure 4 This proves that both Ni and Co in the shell are in an oxidized state. Figure 5 and Figure 6 This proves that both Ni and Co in the inner core are in the metallic state, further proving the formation of the core-shell structure.
[0047] The linear sweep voltammogram of the nickel-cobalt-based core-shell nanomaterial prepared in Example 1 is shown in the attached figure. Figure 7 As shown. When ethanol was added to the 1M potassium hydroxide solution, its catalytic activity was significantly improved, proving that ethanol oxidation occurred. The NMR spectra obtained by electrolysis at different voltages revealed that the product of ethanol oxidation was acetic acid, such as Figure 8 shown.
[0048] The linear sweep voltammetric curves of the nickel-cobalt-based core-shell nanomaterial, the nickel-based core-shell nanomaterial, and the cobalt-based core-shell nanomaterial prepared in Example 1, Comparative Example 1, and Comparative Example 2 in 1M potassium hydroxide + 1M ethanol are as follows: Fig. 9 As shown in Figure 2, the ethanol oxidation activity of the nickel-cobalt-based core-shell nanomaterials is significantly better than that of the nickel-based core-shell nanomaterials and the cobalt-based core-shell nanomaterials. For example, the nickel-cobalt-based core-shell nanomaterials can reach 30 mA cm at only 1.38 V. −2 The current density required for the nickel-based core-shell nanomaterials and cobalt-based core-shell nanomaterials is 1.58V and 1.54V, respectively.
[0049] The charge and discharge curves of the zinc-air battery and zinc-ethanol-air battery assembled with the nickel-cobalt-based core-shell nanomaterials prepared in Example 1 are shown in the attached figure. Fig.10 As shown, it is proved that during the charging process of zinc-air battery, ethanol oxidation reaction is used instead of oxygen evolution reaction, and the charging voltage is only 1.79V, which is much smaller than zinc-air battery (2.1V). It can significantly reduce energy consumption and improve the stability of the battery.
[0050] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a nickel-cobalt-based core-shell catalyst, characterized in that The specific steps are as follows: dissolving soluble nickel salt, soluble cobalt salt, soluble tin salt and soluble citrate in deionized water, stirring and mixing to obtain a mixed solution, using the mixed solution as an electrolyte, adopting a three-electrode system, and using the pretreated carbon cloth as a working electrode to perform constant voltage electrolytic deposition. The voltage range of the constant voltage electrolytic deposition process is 0~-0.4V vs RHE, and the deposition charge is controlled to be 1-8C / cm 2 A nickel-cobalt-tin alloy nanomaterial is generated on the surface of the carbon cloth electrode, and then anodized in an alkaline solution to obtain a nickel-cobalt-based core-shell catalyst, wherein the anodization time is 0.5-3h and the anodization current density is 5-20mA / cm 2 The nickel-cobalt-based core-shell catalyst is used for electrocatalytic ethanol oxidation reaction to produce acetic acid.
2. The method for preparing the nickel-cobalt-based core-shell catalyst according to claim 1, characterized in that: The soluble nickel salt is one or more of nickel sulfate, nickel acetate or nickel nitrate; the soluble cobalt salt is one or more of cobalt sulfate, cobalt acetate or cobalt nitrate; the soluble tin salt is one or more of tin chloride and stannous chloride; the soluble citrate is one or more of sodium citrate or potassium citrate.
3. The method for preparing the nickel-cobalt-based core-shell catalyst according to claim 1, characterized in that: The molar ratio of the soluble nickel salt, the soluble cobalt salt and the soluble tin salt is 1:1:
2.
4. The method for preparing the nickel-cobalt-based core-shell catalyst according to claim 1, characterized in that: The concentrations of the soluble nickel salt and the soluble cobalt salt are both 10-200 mM.
5. The method for preparing the nickel-cobalt-based core-shell catalyst according to claim 1, characterized in that: In the three-electrode system, a graphite rod is used as a counter electrode, and a silver / silver chloride electrode is used as a reference electrode.
6. The method for preparing the nickel-cobalt-based core-shell catalyst according to claim 1, characterized in that: The alkaline solution is one or more of a sodium hydroxide solution or a potassium hydroxide solution, and the concentration of the alkaline solution is 0.1-2M.
7. A nickel-cobalt-based core-shell catalyst, characterized in that: The nickel-cobalt-based core-shell catalyst prepared by the method described in any one of claims 1 to 6 has a unique composition and structure, and its morphology is nanoparticles with NiCoSn alloy as the core and NiCoOOH as the shell.
8. Use of the nickel-cobalt-based core-shell catalyst according to claim 7 as an electrocatalyst for ethanol oxidation reaction.
9. The use according to claim 8, characterized in that: The nickel-cobalt-based core-shell catalyst is directly grown on the carbon cloth. The inner core NiCoSn alloy of the nickel-cobalt-based core-shell catalyst can improve good electrical conductivity and ensure fast and efficient carrier transport. The outer shell NiCoOOH can optimize the adsorption energy of *OH, and the outer shell is rich in defects, which can increase the active specific surface area.
10. The use of the nickel-cobalt based core-shell catalyst according to claim 7 in assembling a zinc-ethanol-air battery, characterized in that: The assembled zinc-ethanol-air battery exhibited excellent charge-discharge activity and cycle stability during the charge-discharge process, with a power density of up to 2.5 mW cm −2 .
Citation Information
Patent Citations
Preparation method of catalyst with core-shell structure for low-temperature fuel cell
CN102500365A
Preparation method of nickel-cobalt alloy and nickel-cobalt oxide solid solution core-shell structure bifunctional electrocatalyst
CN114438544A